STEAM-PROJECTS IN THE DESIGN ACTIVITIES OF PUPILS AND STUDENTS - Kolomiiets, Dmytro; Brovchak, Liudmyla; Shwets, Olena; Babchuk, Yurij (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of the article is to reveal the essence of the new educational style called STEAM (Science, Technology, Engineering, Art, and Mathematics) which was born and now acquires rapid rates on the territory of the world leading countries. Based on the analysis of the main characteristics of STEAM-education and the results of its implementation in the Pedagogical University’s teaching process, it has been stated that STEAM is a synthesis of such previously known teaching methods as contextual, problematic, project, integrated, heuristic education. It has also been shown that at the methodological level STEAM-education integrates such methodological approaches as system, personal, actionable, competence, integrative, technological, communicative, etc. It has been concluded that STEAM-education as being the genuine integration of sciences, technologies, engineering, arts and mathematics, is advisable to use in future teachers’ training process as well as for organizing of project design activities of pupils and students in any branch of industry.